Determinación de los parámetros térmicos de un intercambiador de calor de tubos concéntricos con fluidos orgánico-vapor. - Montaguano Toaquiza, Jonathan Alexis (2018)
The present investigation was carried out for the grinding line in the Tinned Food and Vegetables Factory in Yara municipality, Granma, which belongs to the Basic Business Unit from this province. The objective was aimed at determining the thermic parameters of a heat exchanger (HE) of concentric tubes which permits to guarantee heating and sterilization of organic fluid for the seed-skin separation of some vegetables. In this direction it was proposed a methodology of calculation based on the basic foundations of technical thermodynamics and the heat transference for the subsequent assembling and mounting of heat exchanger at workplace. Among the most relevant outcomes it was obtained a 61% of the machine's efficiency. Other results are identified with the determination of the heat transference area with 6,697 m2. This constitutes a consequence of losses by radiation and convection which are unavoidable in these types of machines of food industry since it is not possible to be thermically isolated to guarantee ailments' inoculation. On the other hand, organic fluids outlet temperatures are maintained according to the normatives between 85°C and 115°C.